2006
DOI: 10.1021/jp065161p
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Characterization of Aluminum-Based Binary Superatoms of Al12X and Their Cluster Salts

Abstract: The geometric and electronic structures of aluminum binary clusters, AlnX (X = Si and P), have been investigated, using mass spectrometry, anion photoelectron spectroscopy, photoionization spectroscopy, and theoretical calculations. Both experimental and theoretical results show that Al12Si has a high ionization energy and low electron affinity and Al12P has a low ionization energy, both with the icosahedral structure having a central Si or P atom, revealing that Al12Si and Al12P exhibit rare-gas-like and alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
103
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 35 publications
(40 reference statements)
12
103
0
Order By: Relevance
“…Gas-phase research has revealed that the doping of a metal core with heteroatoms could affect the stability and physical and chemical properties of the metal clusters. 76 The catalytic activity of polymerstabilized metal clusters is also altered by heteroatom doping (alloying). 18 with a single Pd atom.…”
Section: Determining Heteroatom Doping Effectsmentioning
confidence: 99%
“…Gas-phase research has revealed that the doping of a metal core with heteroatoms could affect the stability and physical and chemical properties of the metal clusters. 76 The catalytic activity of polymerstabilized metal clusters is also altered by heteroatom doping (alloying). 18 with a single Pd atom.…”
Section: Determining Heteroatom Doping Effectsmentioning
confidence: 99%
“…The PES pattern of Al 12 C − was found to be distinctly different, confirming that it does not possess an I h structure. A recent PES and photoionization spectroscopic study by Akutsu et al 21 suggested that Al 12 B − , Al 12 P, and Al 12 P + also have the I h -X@Al 12 structures.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous gas-phase clusters 48 and metal nanoparticles [49][50][51] have been reported where heteroatom doping has led to changes in the physical and chemical properties of the clusters. This is also expected for magic Au n (SR) m clusters.…”
mentioning
confidence: 99%